Tuning rheology and aggregation behaviour of TEMPO-oxidised cellulose nanofibrils aqueous suspensions by addition of different acids - Alves, L. (2021)
The present work intends to study the variations in the rheological properties and aggregation behaviour of TEMPO-oxidised cellulose nanofibrils (CNF) aqueous suspensions, as a function of changes in concentration and systematic changes in the pH, by addition of acids with different anions. It was found that CNF suspensions form strong gels at mass fractions higher than 0.35 % and the gel point is ca. 0.18 %. On the other hand, aggregation is enhanced at acidic pH conditions due to lower charge repulsion among fibrils, leading to an increase of the suspension viscosity. However, distinct rheological behaviours were presented by CNF suspensions as different acids were applied. It was found that phosphate ions resulted in significant aggregation leading to formation of particles of large size and very strong gels, at pH 2.3; distinctly, the presence of acetate ions resulted in lower aggregation, lower particle size and weaker gels, at the same pH value.